Uganda - Developing the Enabling Context for Student Assessment - Kanjee, Anil; Acana, Sylvia (World Bank, Washington, DC, 2014)
Uganda's commitment to improving the quality and outcomes of its education system has translated into a parallel commitment to creating stronger, more sustainable student assessment system, one that includes: (i) examinations for selection and certification; (ii) large scale assessments for monitoring education quality at the country level; and (iii) classroom assessments for evaluating student work and informing ongoing teaching and learning. A number of lessons can be learned from Uganda's experience. First, political stability and a strong commitment to education are key drivers for building a strong assessment system. Second, charging a single institution with all assessment activities can allow for clearer institutional structures, as well as efficient coordination, development, and implementation of assessment programs. Third, competitive salaries need to be in place to attract and retain personnel, and training needs to be provided for capacity building. Finally, a strong focus on student learning and curriculum reforms can act as important catalyst for strengthening the assessment system